Identification of key parameters producing rainfall (MAUSAM, 2013)
o"kkZ ds eq[; izkpyksa dk irk yxkus ds fy, bl 'kks/k i= ls 'kks/kdrkZvksa us m".kdfVca/kh; o"kkZ ekiu fe’ku ¼Vh- vkj- ,e- ,e-½ mixzg vk¡dM+k vk/kkj dh tk¡p dh gSA bl rF; dks le>us ds mijkUr fd c